2019
DOI: 10.1111/gcb.14536
|View full text |Cite
|
Sign up to set email alerts
|

A triple trophic boost: How carbon emissions indirectly change a marine food chain

Abstract: The pervasive enrichment of CO2 in our oceans is a well‐documented stressor to marine life. Yet, there is little understanding about how CO2 affects species indirectly in naturally complex communities. Using natural CO2 vents, we investigated the indirect effects of CO2 enrichment through a marine food chain. We show how CO2 boosted the biomass of three trophic levels: from the primary producers (algae), through to their grazers (gastropods), and finally through to their predators (fish). We also found that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…We observed doubled predatory fish densities under acidified conditions, likely due to bottom-up benefits of high pCO 2 on preys, or some other variables that we did not specifically measure. Our finding agrees with other studies in CO 2 vents reporting an increased biomass of common site-attached carnivorous blennies or triplefins, which was related to a lower abundance of their predators 31 or to the CO 2 -resource effect 32 . Wrasses Figure 5.…”
Section: Discussionsupporting
confidence: 92%
“…We observed doubled predatory fish densities under acidified conditions, likely due to bottom-up benefits of high pCO 2 on preys, or some other variables that we did not specifically measure. Our finding agrees with other studies in CO 2 vents reporting an increased biomass of common site-attached carnivorous blennies or triplefins, which was related to a lower abundance of their predators 31 or to the CO 2 -resource effect 32 . Wrasses Figure 5.…”
Section: Discussionsupporting
confidence: 92%
“…This study was carried out between April 2014 and July 2015 in shallow P. oceanica meadows at CO 2 vents off the Castello Aragonese isle (Ischia Island, 40°43′51.01″N, 13°57′48.07″E; Tyrrhenian Sea, Italy). Submarine vents have been extensively used to assess the effects of naturally acidified seawater on biological communities as they are characterized by the emission of gases into seawater, predominantly CO 2 , which create gradients in pH and carbonate chemistry, without confounding gradients of other environmental variables, such as temperature, salinity, hydrodynamic conditions, and toxic hydrogen sulfide (Hall‐Spencer et al ; Fabricius et al ; Russell et al ; Milazzo et al ; Doubleday et al ). In particular, in the last decade, previous studies carried out at Ischia Island vents have shown that areas exposed to CO 2 bubbling do not differ from control areas in terms of salinity (38‰), temperature (seasonal fluctuations of 14–25°C), light (~ 7500 lx d −1 ), and total alkalinity (2.5 mequiv.…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that smaller body size is a physiological adaptation to environmental acidification in order to maintain calcification as well as to have the energy to repair shell dissolution (Garilli et al ., 2015). For herbivorous gastropods living at vent sites, the enhanced algal food levels due to high CO 2 can buffer, to a variable extent, the negative effect of OA on calcification (Doubleday et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%